(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2025)
The article presents the results of research of the formulation of ingredient composition for the dessert products production using cottage cheese mousse with added dietary fiber as an example. The relevance of this work is determined by the modern society’s need for food products that combine high nutritional and biological value with attractive organoleptic characteristics. Among various directions of recipe improvement, particular importance is given to the use of natural functional ingredients, specifically plant-based dietary fibers, which positively affect the product structure, its stability, and nutritional value. Cottage cheese mousse was selected as the research object. It is characterized by a delicate texture and high biological value due to the content of complete milk proteins. Traditional cottage cheese mousse receipts have certain disadvantages which are structural instability during storage, risk of whey separation, and elevated fat content, which reduces their dietary appeal. For enhancing the technological and consumer properties, citrus fiber was incorporated into the receipt as a natural source of dietary fiber. Its main properties include high water and fat absorption ability, emulsifying ability, ability to stabilize consistency, and prevention of syneresis. The study demonstrated that the addition of citrus fiber in the amount of 0.5…1.2% of the mixture mass allows achieving an optimal balance between maintaining delicate and light texture and improving structural and mechanical properties. At this concentration, the mousse was characterized by homogeneous consistency, elasticity, and absence of moisture separation during storage. Increasing the fiber content above 1.5…2.0% resulted in undesirable changes: excessive thickness, reduced airiness, and the appearance of a floury mouthfeel, which negatively affected the organoleptic properties of the dessert. A model of the recipe composition of cheese mousse with the addition of citrus fiber was developed.